PEMASANGAN PENDINGIN AIR DENGAN KENDALI SUHU PADA PERKEBUNAN GREENFARM HYDROPONIC GUNUNGPATI KOTA SEMARANG: PEMASANGAN PENDINGIN AIR DENGAN KENDALI SUHU PADA PERKEBUNAN GREENFARM HYDROPONIC GUNUNGPATI KOTA SEMARANG - Aggie Brenda Vernandez; Eriko Arvin Karuniawan; Pangestuningtyas Diah Larasati; Aminuddin Rizal (Politeknik Negeri Semarang, 2026)
The community service activity conducted with the partner GreenFarm Hydroponic aims to address the partner’s issue of conventional temperature regulation in the hydroponic system, where temperature levels fluctuate depending on environmental conditions. This instability reduces dissolved oxygen levels and inhibits plant growth. The activity includes training on the installation and operation of an automatic water-cooling system. The developed cooling system utilizes an Outseal Mega V2 Slim, NodeMCU ESP32, DS18B20 temperature sensor, evaporator chiller, outdoor AC unit, LCD, relay, contactor, and Blynk-based monitoring. This device is capable of maintaining water temperature at the ideal level of 27°C through both automatic and manual modes. The implementation of this technology not only enhances temperature stability and production quality but also facilitates remote monitoring and reduces manual intervention. This program demonstrates the role of vocational higher education in providing practical technological solutions that support the sustainability of hydroponic enterprises. The activity was successfully carried out, with GreenFarm Hidroponik now able to operate the automatic cooling system either via panel buttons or through the Blynk IoT application.